Pengaruh Disiplin dan Motivasi Kerja Terhadap Kinerja Pegawai Kantor Sekretariat Daerah Kabupaten Sumenep - Al Furqon, Ramadhani; Mudji, Kuswinarno (Management Department of Economics and Business Of Trunojoyo Madura University, 2024)
egional Secretariat of Sumenep District, is the Regional Government which is the organization of governmental affairs, by the local government and the DPRD according to the basis of autonomy and the duty of assistance with the principle of autonomousness in the system and principles of the Union State of the Republic of Indonesia in the UUD of the State of Indonesia. The regional secretariat office of Sumenep district should have good official performance. Starting with the work discipline of the staff, and the work motivation required by the staff. This study aims to identify and analyze the influence of work discipline and motivation on the performance of the staff of the Regional Secretariat of Sumenep District. The aim of this study is to find out the Impact of Work Discipline and Motivation of Work on performance of employees of the regional secretariat of the Sumeneb District, partially and simultaneously. The study uses a quantitative method with a survey of respondents from the Office of the Regional Secretariat of Sumenep District. Technique of data collection of 67 respondents using Slovin formulas. Data collection methods through interviews, questionnaires and library studies. The data analysis techniques used are Validity Test, Reliability Test, Normality Test, Multicolinerity test, Heteroskedastisity Tests, Double Linear Regression Test, Hypothesis Tests. The results of the study are: (1) Partially Working Discipline (individual) has a positive and significant impact on the performance of the staff of the Sumenep District Secretariat with a t-value of 5,173 t table 1,66864 as well as a level of significance of 0,000 0,05 with a beta value of 0,450. (2) Partially working motivation of the Secretariat of Sumenip District with a counting value of 5,618 t Table 1,66864, and a significant level of 0.000 0.05 with a Beta value of 0.489.